Water vapor absorption in the region of the oxygen A-band near 760 nm. (November 2021) - Vasilchenko, S.; Mikhailenko, S.N.; Campargue, A.
Highlights: High sensitivity absorption spectra of water vapor in the region of the A-band of oxygen near 760 nm. About 600 water lines are measured rovibrationally assigned between 12969 and 13170 cm -1 . The detection threshold corresponds to line intensities smaller than to 1×10 -29 cm/molecule. 103 upper energy levels of H2 16 O are newly determined and 134 energy levels are corrected. A line list of 693 transitions of H2 16 O, H2 18 O and HD 16 O is recommended for the considered region. Abstract: The oxygen A-band near 760 nm is used to determine the air-mass along the line of sight from ground or space borne atmospheric spectra. This band is located in a spectral region of very weak absorption of water vapor. The increased requirements on the determination of the air columns make suitable to accurately characterize water absorption spectrum in the region. In the present work, we use a cavity ring down spectrometer newly developed in Tomsk, to measure with unprecedented sensitivity and accuracy the water spectrum in the 12969 - 13172 cm −1 region. While about fifty transitions were previously detected in the region, a total of about 580 water lines are measured by CRDS and rovibrationally assigned, leading to the determination of 103 new levels and correction of 134 levels of H2 16 O. Spectroscopic line lists available in the region (HITRAN, W2020 and theoretical line lists) show some important deviations compared to observations. In particular, line intensities are poorly predicted by available ab initio calculations for transitions involving a highly bending excitation. Graphical abstract: Image, graphical abstract